2014
DOI: 10.1039/c4nr03057e
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured metal sulfides for energy storage

Abstract: Advanced electrodes with a high energy density at high power are urgently needed for high-performance energy storage devices, including lithium-ion batteries (LIBs) and supercapacitors (SCs), to fulfil the requirements of future electrochemical power sources for applications such as in hybrid electric/plug-in-hybrid (HEV/PHEV) vehicles. Metal sulfides with unique physical and chemical properties, as well as high specific capacity/capacitance, which are typically multiple times higher than that of the carbon/gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
506
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 927 publications
(526 citation statements)
references
References 391 publications
2
506
0
6
Order By: Relevance
“…Moreover, the necessary addition of conductive additives and binders inevitably lessens overall energy storage capacity, and binders in particular hinder electron transport from MS nanostructures to the electron collector, limiting their practical applications. 16,17 Recently, direct growth of self-supported NiCo 2 O 4 nanowires and ZnCo 2 O 4 nanowire arrays on current-collecting substrates has been shown to overcome the drawbacks of mixing active electrode materials with conductive additives and binders and to increase endurance of fast charge and discharge processes. 22,23 Furthermore, it has been reported that 3D network structures (for example, graphene networks, 7 MO/3D graphene network composites 24 and diamond/ carbon nanotubes 25 ) can provide open channels for efficient electron/ ion transport and large surface area for reactions, both of which are favorable properties for materials and devices used in electrochemical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the necessary addition of conductive additives and binders inevitably lessens overall energy storage capacity, and binders in particular hinder electron transport from MS nanostructures to the electron collector, limiting their practical applications. 16,17 Recently, direct growth of self-supported NiCo 2 O 4 nanowires and ZnCo 2 O 4 nanowire arrays on current-collecting substrates has been shown to overcome the drawbacks of mixing active electrode materials with conductive additives and binders and to increase endurance of fast charge and discharge processes. 22,23 Furthermore, it has been reported that 3D network structures (for example, graphene networks, 7 MO/3D graphene network composites 24 and diamond/ carbon nanotubes 25 ) can provide open channels for efficient electron/ ion transport and large surface area for reactions, both of which are favorable properties for materials and devices used in electrochemical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with their MO counterparts, MSs generally feature higher electrical conductivity, better mechanical and thermal stability, and richer redox chemistry, making them attractive anode materials for high-performance LIBs. 16,17 Various MS nanostructures including nanoparticles, 18 nanosheets, 19 nanowires, 20 and nanotubes 21 have been synthesized and offer superior electrochemical energy storage capacity compared with bulk MSs. However, the large volumetric change of MS nanostructures during electrochemical reactions leads to reduced capacity and poor cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical performances of supercapacitors mainly depend on the property of electrode materials, including carbon materials, conducting polymers and transition metal oxides/hydroxides/sulfides [4]; Among them, transition metal oxides/sulfides (such as MoS 2 [5], CuS [6], Ni 3 S 2 [7]) are the most promising candidate materials for supercapacitors. Compared with binary metal oxides/sulfides, ternary metal oxides/sulfides exhibit much higher specific capacitance owing to the rich redox reaction sites of their mixed valence and the synergistic effect of different cations [8]. Very recently, NiCo 2 S 4 attracts much interest since its electrical conductivity is nearly 100 times higher than that of NiCo 2 O 4 , which has a significant impact on its excellent electrochemistry performance [9] and [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, similar to the classical Mott-Hubbard insulator FeO [10,11], FeS is considered to be an important material for solid state and earth sciences. Apart from this, hexagonal iron monosulfide has also been investigated in field as diverse as applied surface sciences [12] or as potential material for future energy storage and lithium-ion battery applications [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, similar to the classical Mott-Hubbard insulator FeO [10,11], FeS is considered to be an important material for solid state and earth sciences. Apart from this, hexagonal iron monosulfide has also been investigated in field as diverse as applied surface sciences [12] or as potential material for future energy storage and lithium-ion battery applications [13].As revealed by high-pressure x-ray diffraction measurements [1,3,5,14], FeS undergoes a series of structural phase transitions with increasing pressure (P): a detailed description of the × P T structural phase transformations of FeS can be found, for example, in [2] and [5]. From these studies it is known that under ambient conditions troilite FeS has a hexagonal structure (space group P − 62c) which is derivative of the NiAs unit cell with axis lengths = =å c 3 5.955 A f and =c 2 11.76 A f [14], where c f is the lattice parameter of the fundamental NiAs subcell.…”
mentioning
confidence: 99%